Does productivity level influence the economic impacts of price support policies in Ethiopia? - Emerta Aragie; Jean Balié; Emiiano Magrini (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2019)
This study follows from the recent move by most developing economies to introduce price support programs for selected cereals. For Ethiopia, we examine the price, quantity, welfare and government intervention effects of alternative producer and consumer price policies backed-up by public cereal storage services when agriculture is faced with positive and negative productivity shocks. We find that producer price support policies are production enhancing. However, these policies work against the urban poor and rural net-buyers as food prices could not fall anymore beyond the level dictated by the support program. Meanwhile, consumer price support policies tend to harm rural households due to further losses in incomes as the control on consumer prices supresses producer prices. The analysis further shows that consumer price stabilisation policies aggravate food insecurity since domestic cereal production declines strongly.
Keywords: 330; price support policies; public storage; agriculture; CGE; distributional effect